2010
DOI: 10.3998/ark.5550190.0011.b23
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of bioisosteric 5-sulfa-rutaecarpine derivatives

Abstract: Rutaecarpine (Evodia rutaecarpa) derivatives were synthesized by bioisosteric replacements of the quinazolone moiety of the pentacyclic system with benzothiadiazine 1,1-dioxide. Syntheses were performed efficiently by formation of phenylhydrazones via active methylene group transformations of pyrrolo-and pyrido[1,2-b]1,2,4-benzothiadiazine 5,5-dioxides, and subsequent Fischer-indolization. Preliminary testing of compound 3 showed cytotoxic activity against HeLa cells and apoptosis inducing effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Bioisosteric replacement of the quinazolinone moiety of the pentacyclic system with benzothiadiazine 1,1-dioxide has been pursued [48] (Scheme 10). Bubenyák et al reported a condensation of benzothiadiazine 1,1-dioxide analogue 23 with phenyldiazonium chloride led to a phenylhydrazone derivative, which was subjected to Fischer indole synthesis to afford the corresponding 5-sulfarutaecarpine ( 24 ).…”
Section: Synthesis Of Rutaecarpinementioning
confidence: 99%
See 1 more Smart Citation
“…Bioisosteric replacement of the quinazolinone moiety of the pentacyclic system with benzothiadiazine 1,1-dioxide has been pursued [48] (Scheme 10). Bubenyák et al reported a condensation of benzothiadiazine 1,1-dioxide analogue 23 with phenyldiazonium chloride led to a phenylhydrazone derivative, which was subjected to Fischer indole synthesis to afford the corresponding 5-sulfarutaecarpine ( 24 ).…”
Section: Synthesis Of Rutaecarpinementioning
confidence: 99%
“…It should be noted that an isostere 24 with a sulfone moiety was not as active as rutaecarpine. The percentage of apoptotic cells corresponding to the sub-GI phase of 5-sulfarutaecarpine was found to be 29.2%, which compares with the 14.5% of rutaecarpine [48]. In addition, the hybrids 27a showed an increase of cytotoxic activities against HeLa cells and apoptosis inducing effects at a concentration comparable to that of etoposide.…”
Section: Biological Propertiesmentioning
confidence: 99%
“…Gyűjtő et al synthesized several benzothiadiazines via the lithiation method by reacting 2‐bromo benzaldehyde with ethylene glycol in toluene at reflux temperature in the presence of p ‐toluenesulfonic acid to produce ortho ‐brominated acetal‐protected benzaldehyde (2‐bromo benzyl–1,3‐dioxolane) [11]. Tricyclic benzothiadiazines were synthesized starting from veleroactam and 2‐nitrobenzene sulfonyl chloride [12]. These two last methods used prefunctionalized starting materials.…”
Section: Introductionmentioning
confidence: 99%